Gene cloning and DNA analysis : an introduction - Brown, T. A. (Terence A.) (Hoboken, NJ : Wiley-Blackwell, 2021)
"The main development in DNA technology since publication of the Seventh Edition of Gene Cloning has been the increased use of gene editing as a tool in both research and biotechnology. The basic methodology for CRISPR editing is now described in Chapter 12 and the applications of the method are explored, in the context of plant genetic engineering, in Chapter 16. Elsewhere, the continuing evolution of next-generation DNA sequencing is reflected by a reorganization of this part of Chapter 10, and to deal with the further proliferation of methods for studying transcriptomes and proteomes (albeit not strictly DNA Analysis) I have created a new chapter devoted to these methods. Other additions include new sections on melt curve analysis of real-time PCR products and genetic typing of human disease mutations"--
Why gene cloning and DNA analysis are important -- Vectors for gene cloning : plasmids and bacteriophages -- Purification of DNA from living cells -- Manipulation of purified DNA -- Introduction of DNA into living cells -- Cloning vectors for Escherichia coli -- Cloning vectors for eukaryotes -- How to obtain a clone of a specific gene -- The polymerase chain reaction -- Sequencing genes and genomes -- Studying gene expression and function -- Studying genomes -- Studying transcriptomes and proteomes -- Production of protein from cloned genes -- Gene cloning and DNA analysis in medicine -- Gene cloning and DNA analysis in agriculture -- Gene cloning and DNA analysis in forensic science and archaeology.
Includes bibliographical references and index.
MNS
Karim International
Keywords: Cloning, Molecular; Sequence Analysis, DNA; DNA, Recombinant -- Analysis; DNA -- Analysis; Nucleotide sequence; Molecular cloning